Metal-Binding Proteins Cross-Linking with Endoplasmic Reticulum Stress in Cardiovascular Diseases - Kejuan Li; Yongnan Li; Hong Ding; Jianshu Chen; Xiaowei Zhang (Journal of Cardiovascular Development and Disease, 2023)
The endoplasmic reticulum (ER), an essential organelle in eukaryotic cells, is widely distributed in myocardial cells. The ER is where secreted protein synthesis, folding, post-translational modification, and transport are all carried out. It is also where calcium homeostasis, lipid synthesis, and other processes that are crucial for normal biological cell functioning are regulated. We are concerned that ER stress (ERS) is widespread in various damaged cells. To protect cells’ function, ERS reduces the accumulation of misfolded proteins by activating the unfolded protein response (UPR) pathway in response to numerous stimulating factors, such as ischemia or hypoxia, metabolic disorders, and inflammation. If these stimulatory factors are not eliminated for a long time, resulting in the persistence of the UPR, it will aggravate cell damage through a series of mechanisms. In the cardiovascular system, it will cause related cardiovascular diseases and seriously endanger human health. Furthermore, there has been a growing number of studies on the antioxidative stress role of metal-binding proteins. We observed that a variety of metal-binding proteins can inhibit ERS and, hence, mitigate myocardial damage.